2021
DOI: 10.3390/en14082246
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hydrocarbon-Degrading Consortia from Surface and Deep Waters of the Eastern Mediterranean Sea: Characterization and Degradation Potential

Abstract: The diversity and degradation capacity of hydrocarbon-degrading consortia from surface and deep waters of the Eastern Mediterranean Sea were studied in time-series experiments. Microcosms were set up in ONR7a medium at in situ temperatures of 25 °C and 14 °C for the Surface and Deep consortia, respectively, and crude oil as the sole source of carbon. The Deep consortium was additionally investigated at 25 °C to allow the direct comparison of the degradation rates to the Surface consortium. In total, ~50% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Indeed, prior exposure of the inoculum to the pollutant caused an adaptation of the microorganisms to utilize the hydrocarbons as carbon and energy sources, shortening the lag phase and accelerating the beginning of the exponential phase [57]. Furthermore, Charalampous et al [58] in a recent work reported differences in hydrocarbons removal between shallow and deep sediment consortia (50-58% and 33-42%, respectively), highlighting the role of consortium origin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior exposure of the inoculum to the pollutant caused an adaptation of the microorganisms to utilize the hydrocarbons as carbon and energy sources, shortening the lag phase and accelerating the beginning of the exponential phase [57]. Furthermore, Charalampous et al [58] in a recent work reported differences in hydrocarbons removal between shallow and deep sediment consortia (50-58% and 33-42%, respectively), highlighting the role of consortium origin.…”
Section: Discussionmentioning
confidence: 99%
“…We developed and successfully employed a high-pressure apparatus for sampling and experimentation with seawater that was collected from depths down to 1000 m, without any pressure disruptions during sample retrieval and with an uninterrupted pressure flow between each step. Our previous work with enriched consortia from the deep waters of EMS [44] showed their capability for effective crude oil bioremediation in the case of an oil spill. Following this work and focusing on a real-life scenario of a deepsea oil release where oil is entrapped in plumes, we successfully proved that indigenous microbial populations from EMS are readily available to combat subsea oil spills.…”
Section: Discussionmentioning
confidence: 99%
“…EMS faces new challenges, as existing oil and gas reserves in the area, along with the intensification of offshore oil and gas exploration activities in deep and ultra-deep waters, pose a threat for an accidental oil release in the deep-sea environment. Our current knowledge on microbial response in the deep EMS is still very limited [42][43][44] and the so-far available biodegradation rates derive from our previous work on enriched deep-water consortia that are grown at atmospheric pressure [44]. EMS consortia that were collected from surface and deep waters in our previous work showed that the latter resulted in a higher efficiency for hydrocarbon degradation within the first week following oil contamination [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method followed for DNA extraction has been previously described in Charalampous et al [26]. In summary, membrane filters were vortexed in CTAB extraction buffer, followed by three freeze-thaw cycles.…”
Section: Methodsmentioning
confidence: 99%